أثر الملوثات الطبية السائلة المتخلفة عن المستشفيات الحكومية في تلوث البيئة المائية في مدينة البصرة - المياحي، إيمان كريم عباس (جامعة البصرة - مركز دراسات البصرة والخليج العربي, 2020)
تم دراسة المستشفيات الحكومية الكبرى في مدينة البصرة وهي مستشفى (البصرة العام، التعليمي، الموانئ، البصرة التخصصي النسائية والولادة، الفيحاء، الشفاء، ومستشفى البصرة التخصصي للأطفال) التي تطرح يوميا كميات كبيرة من المخلفات السائلة التي يفترض ان تطرح الى وحدات معالجة هذه المياه الخاصة بالمستشفيات من خلال إجراء مسح نوعي وكمي للمياه المطروحة من هذه المستشفيات وذلك بأخذ عينتين من المياه في شهري كانون الثاني وحزيران لكل مستشفى لعام ٢٠١٦، كما ان المخلفات السائلة للمستشفيات سجلت زيادة في تراكيز المواد العالقة (T.S.S) والمواد الذائبة (T.D.S) والمتطلب الحيوي والكيمياوي للأوكسجين والكلوريدات، أما عنصري الكبريتات والفوسفات شهدت ارتفاعا في قيمتها في بعض المستشفيات بينما الدالة الحامضية (PH) وعنصر النترات (NO3) لم تتجاوز الحدود البيئية المسموح بها لهذه العناصر، كما توصلت الدراسة الى معرفة كمية المياه المطروحة من المستشفيات الحكومية الكبرى ووجهات التصريف النهائي لهذه المياه اذ تبين ان اغلب المستشفيات المدروسة تفتقر الى وحدات معالجة نظامية لمخلفاتها السائلة وان وجدت فأنها تتوقف بين فترة وأخرى او تعالج جزءا من المياه وتطرح الباقي دون معالجة الى المجاري العامة أو الى احواض تعفين يتم سحبها بواسطة سيارات حوضية أو تطرح عن طريق انابيب الى الخارج بالقرب من المستشفى، كما في مستشفى الفيحاء او تطرح الى الانهر والمبازل القريبة منها كما في مستشفى التعليمي ومستشفى الموانئ.
The major governmental hospitals in the city of Basra have been studied, which are (Basra General, Teaching, Ports, Basra Specialized Gynecology and Childbirth Hospital, Al-Fayhaa, Al-Shifa, and Basra Specialized Hospital for Children) that give daily large quantities of liquid wastes that are supposed to be thrown into the treatment units of this special water. In hospitals, by conducting a qualitative and quantitative survey of the discharged water from these hospitals by taking two samples of water in the months of January and June for each hospital for the year 2016, and hospital liquid wastes recorded an increase in the concentrations of suspended matter (TSS) and dissolved materials (TDS) and the biological and chemical requirement for oxygen. And chlorides, as for the components of sulfate and phosphate, an increase in their value has occurred in some hospitals, while the acidic function (PH) and the element nitrate (NO3) did not exceed the permissible environmental limits for these elements, and the study also found the quantity of water discharged from major government hospitals and the final disposal destinations for this water. It was found that most of the studied hospitals lack regular treatment units for their liquid wastes, and if they are found, they stop from time to time or treat c Part of the water is discarded without treatment into public sewers or septic basins that are withdrawn by tank trucks or thrown through pipes to the outside near the hospital, as in Al-Fayha Hospital, or thrown into rivers and nearby homes, as in the teaching hospital and the port hospital
Keywords: النظام البيئي -- الملوثات الطبية السائلة -- المستشفيات الحكومية -- التلوث البيئي -- البيئة المائية -- مدينة البصرة